Plan de exportación de gases criogénicos a Perú - Corella Lascano, Edgar Andrés (2017)
The present titling work is focused on promoting and encouraging exports of non-traditional Ecuadorian products. All the process and the elaboration of the cryogenic gases and their percentages in the air will be indicated. Statistical data will be analyzed based on the export from Ecuador to South America, especially Peru, and will also investigate import data by the country of destination hoping to find the process that was used for marketing If the cryogenic gases a care product in its handling and transfer will indicate the way of packaging to its final destination. Everything related to logistics, export processes, permit requirements, paperwork, incoterms, packaging, means of transportation more optimal and safe to reach the destination will also be developed. Finally, it will be recommended how to improve the export of this type of products, in addition to promoting the development of our producers to generate a greater production and to have quality and to be a competition with this product, also to recommend that for good commercialization we must have good and strategic alliances for That the process is done quickly and without any impediment.